P–677 Endometrial thickness, endometrial preparation protocol and number of euploid embryos transferred, significantly impact the live birth in frozen embryo transfer cycles. (6th August 2021) - Liñá. Tegedor, A; Elkhatib, I; Abdala, A; Bayram, A; Ab. Ali, K; Arnanz, A; Ruiz, F; Melado, L; Lawrenz, B; Munck, N D; Fatemi, H M
Abstract: Study question: Is the live birth rate (LBR) in euploid frozen embryo transfer (FET) cycles affected by the endometrial thickness (EMT)? Summary answer: A significantly higher LBR was observed in patients with an endometrial thickness of at least 7.5mm (46.24% vs. 54.63%) What is known already: Parameters assessing the endometrium prior planning a FET include endometrial thickness, pattern and blood flow. The impact of the endometrial thickness on ART outcomes is controversial, with conflicting results published. A recent meta-analysis evaluated whether EMT could predict pregnancy outcomes and suggested that lower EMT was associated with lower incidence of clinical pregnancy rate (CPR), implantation rate (IR) and LBR. Due to heterogeneity of parameters evaluated between different publications, where embryos with unknown ploidy status were transferred, in conjunction with variability of stimulation protocols and the number of embryos transferred, the real effect of the EMT was difficult to infer. Study design, size, duration: This was a two-center retrospective observational study including a total of 1522 euploid FET cycles between March 2017 and March 2020 at ART Fertility Clinics Muscat, Oman and Abu Dhabi, UAE. Participants/materials, setting, methods: Trophectoderm biopsies were analyzed with Next Generation Sequencing (NGS). Vitrification/warming of blastocysts was performed using Cryotop method (Kitazato). EMT was measured by vaginal ultrasound prior initiating the progesterone administration (± 1 day) and LBR was recorded. Multivariate analysis was performed between LB outcomes and median EMT while controlling for confounding factors. Main results and the role of chance: A total of 1522 FET cycles were analyzed: 975 single embryo transfer (SET) and 547 double embryo transfer (DET). The mean age of the patients was 33.38 years with a mean BMI of 27.1 kg/m2. FET were performed in EMT ranging from 3 to 15 mm and 50.52% resulted in a live birth. Though potentially all ranges of EMT were associated with LB, the median EMT in patients with LB was significantly higher than the median EMT of patients without LB (7.6mm vs. 7.4mm; p < 0.001). The dataset was stratified into two groups based on the median EMT (7.5mm): < 7.5mm (n = 744 cycles) and ≥ 7.5mm (n = 778 cycles). A significantly higher live birth rate was observed in ≥ 7.5mm group (46.24% vs. 54.63%. p = 0.0012). In multivariate analysis, EMT, FET endometrial preparation protocol, and number of embryos transferred were the main parameters influencing the chance to achieve LB: OR 1.10 [1.01–1.19], p < 0.015 for the EMT; OR 1.84 [1.47–2.30], p < 0.0001 for Natural Cycle protocol and OR 1.55 [1.25–1.93], p < 0.0001 for DET. Intercept 0.18 [0.07–0.44] p < 0.0002. Female age did not reach significance: OR 1.02 [1.00–1.04], p = 0.056. Limitations, reasons for caution: Besides the retrospective nature of the study, the inter-observer variability in EMT assessment between different physicians is a limitation. The physician and embryologist performing the embryo transfer could not been standardized due to the multicenter design of the study. Wider implications of the findings: The EMT in FET may influence the LBR and should be considered as an important factor for the success of embryo transfer cycles. Whether these results can be extrapolated to fresh embryo transfer and to blastocysts with unknown ploidy status, needs further investigation. Trial registration number: Not applicable